# The result of subtracting 2 from its opposite is _____. 0 1 4 -4

QUESTION POSTED AT 14/02/2020 - 03:51 PM

QUESTION POSTED AT 14/02/2020 - 03:51 PM

The result would be zero, because 2 - 2 is the same as 2 +(-2).

I hope this helps you

ANSWERED AT 28/02/2020 - 07:08 AM

QUESTION POSTED AT 28/02/2020 - 07:08 AM

The diagonal is the distance between opposite corners...

d=x^2+y^2

d^2=260100

d=510 feet

d=x^2+y^2

d^2=260100

d=510 feet

ANSWERED AT 28/02/2020 - 06:50 AM

QUESTION POSTED AT 28/02/2020 - 06:50 AM

C. Adding to x shift graph left, subtracting from x shifts graph right. Adding a constant shifts the graph upwards and subtracting a constant shifts graph downwards...

In this case f(x) is shifted leftward by 11 units and downward by 6 units.

In this case f(x) is shifted leftward by 11 units and downward by 6 units.

ANSWERED AT 28/02/2020 - 06:48 AM

QUESTION POSTED AT 28/02/2020 - 06:48 AM

19 times will be the amount of pennies

ANSWERED AT 28/02/2020 - 06:45 AM

QUESTION POSTED AT 28/02/2020 - 06:45 AM

1. 2x-4=10

+4

2x=14

÷2

×=7

2. -17x+16=58

-16

-17x= 42

×=-2.47

3. 4-9x=-14

x=5.5

+4

2x=14

÷2

×=7

2. -17x+16=58

-16

-17x= 42

×=-2.47

3. 4-9x=-14

x=5.5

ANSWERED AT 28/02/2020 - 06:33 AM

QUESTION POSTED AT 28/02/2020 - 06:33 AM

The answer is rectangle because the top and bottom sides are long and the sides are sort.

ANSWERED AT 28/02/2020 - 06:20 AM

QUESTION POSTED AT 28/02/2020 - 06:20 AM

**Answer: She will pay $ 720 for the computer.**

**Step-by-step explanation:**

Since, the cost price of the laptop = $ 900,

Also, after getting the $ 100 gift card,

The new price of the laptop = $ 900 - $ 100 = $ 800

According to the question,

The store is offering 10% off on all computers.

The final price of the laptop = 800 - 10% of 800

= 800 - 80

= $ 720,

Hence, **$ 720 will be paid for the laptop.**

ANSWERED AT 28/02/2020 - 06:18 AM

QUESTION POSTED AT 28/02/2020 - 06:18 AM

On a coordinate plane, any movement up and down is on the y-axis. So if your parallelogram is moving down 2.5 units, then the y-values of each vertice will go down by 2.5:

A(-2, -8), B(-4, -8), C(-3, -4.5), D(-1, -4.5)

A(-2, -8), B(-4, -8), C(-3, -4.5), D(-1, -4.5)

ANSWERED AT 28/02/2020 - 06:15 AM

QUESTION POSTED AT 28/02/2020 - 06:15 AM

**Answer: 30%. I go to K12 and just take the test and got it right.**

ANSWERED AT 28/02/2020 - 06:15 AM

QUESTION POSTED AT 28/02/2020 - 06:15 AM

1. 1/4

2. 3/8

3. 8/8

4.5/8

2. 3/8

3. 8/8

4.5/8

ANSWERED AT 28/02/2020 - 05:57 AM

QUESTION POSTED AT 28/02/2020 - 05:57 AM

80+20 equals 100. Brainliest!!!!!!

ANSWERED AT 28/02/2020 - 05:51 AM

QUESTION POSTED AT 28/02/2020 - 05:51 AM

The answer is 4x^2-13x+14

ANSWERED AT 28/02/2020 - 05:51 AM

QUESTION POSTED AT 28/02/2020 - 05:51 AM

(417.25-32)*150/100)+32=609.88

ANSWERED AT 28/02/2020 - 05:48 AM

QUESTION POSTED AT 28/02/2020 - 05:48 AM

B. This is because length is represented by X in a coordinate grid. X is always the first point in a coordinate set. 4 + 1 is you equation to determine the length.

ANSWERED AT 28/02/2020 - 05:45 AM

QUESTION POSTED AT 28/02/2020 - 05:45 AM

3) Since all the sides are equal in an equilateral triangle, you can just say they're all "x". Since the perimeter is the length around the shape, x+x+x=12in. You can then solve the equation to get x=4

ANSWERED AT 28/02/2020 - 05:22 AM

QUESTION POSTED AT 28/02/2020 - 05:22 AM

Part A : add side 1 to side 2

8x^2 - 5x - 2 + 7x - x^2 + 3 ....combine like terms

7x^2 + 2x + 1 <=== total of side 1 + side 2

part B : since perimeter is the sum of all sides, we can find the third side by subtracting the sum of the 2 sides (from part A) from the perimeter.

4x^3 - 3x^2 + 2x - 6 - (7x^2 + 2x + 1)...distribute thru the parenthesis

4x^3 - 3x^2 + 2x - 6 - 7x^2 - 2x - 1 =....combine like terms

4x^3 - 11x^2 - 7 <===length of 3rd side

part C : Polynomials are closed under addition and subtraction because when adding/subtracting polynomials, the result is another polynomial.

8x^2 - 5x - 2 + 7x - x^2 + 3 ....combine like terms

7x^2 + 2x + 1 <=== total of side 1 + side 2

part B : since perimeter is the sum of all sides, we can find the third side by subtracting the sum of the 2 sides (from part A) from the perimeter.

4x^3 - 3x^2 + 2x - 6 - (7x^2 + 2x + 1)...distribute thru the parenthesis

4x^3 - 3x^2 + 2x - 6 - 7x^2 - 2x - 1 =....combine like terms

4x^3 - 11x^2 - 7 <===length of 3rd side

part C : Polynomials are closed under addition and subtraction because when adding/subtracting polynomials, the result is another polynomial.

ANSWERED AT 28/02/2020 - 05:21 AM

QUESTION POSTED AT 28/02/2020 - 05:21 AM

Hello :

-4x² +7x-8 = 0

delta = b²-4ac a=-4 b=7 c=-8

delta = (7)²-4(-4)(-8) =-79

(delta) < 0... no solution in : R

-4x² +7x-8 = 0

delta = b²-4ac a=-4 b=7 c=-8

delta = (7)²-4(-4)(-8) =-79

(delta) < 0... no solution in : R

ANSWERED AT 28/02/2020 - 05:14 AM

QUESTION POSTED AT 28/02/2020 - 05:14 AM

The answer is D I am almost positive

ANSWERED AT 28/02/2020 - 05:05 AM

QUESTION POSTED AT 28/02/2020 - 05:05 AM

Answer : **A {-8}**

-4 = b/2

-4 *2 = b

**-8 = b**

-4 = b/2

-4 *2 = b

ANSWERED AT 28/02/2020 - 05:01 AM

QUESTION POSTED AT 28/02/2020 - 05:01 AM

I believe it would be (B) sometimes...

But I'm not %100 positive it is right,

But I'm not %100 positive it is right,

ANSWERED AT 28/02/2020 - 04:58 AM

QUESTION POSTED AT 28/02/2020 - 04:58 AM

**Answer:**

We have to find the number of solutions of each of the following equations by observing their graphs.

We know that the number of real solutions are the number of times the graph touches the x-axis. i.e. the point at which the function is zero.

**1)**

Clearly this graph has no real solutions.

Also we can see from the equation that the function takes no real value such that the function is zero.

since,

Hence, it has **no real solution.**

**2)**

This graph has one real solution i.e. 0 with multiplicity 2.

Also it could be seen as:

are the possible solution of the equation.

Hence,** the function has one real solution with multiplicity 2.**

**3)**

From the graph of this function we see that **it has 2 real solutions** i.e. 4 and -4.

( Also it could be seen as:

)

ANSWERED AT 28/02/2020 - 04:44 AM

QUESTION POSTED AT 28/02/2020 - 04:44 AM

-4x + 15 > 59

-4x > 44

x < -11 - switch the inequality when dividing or multiplying by a negative number

-4x > 44

x < -11 - switch the inequality when dividing or multiplying by a negative number

ANSWERED AT 28/02/2020 - 04:34 AM

QUESTION POSTED AT 28/02/2020 - 04:34 AM

1. Factor out common terms in the first two terms, then in the last two terms

x^2(6x^2-5)+2(6x^2-5)

2. Facto out the common term 6x^2-5

(6x^2-5)(x^2+2)

Have a nice day :D

x^2(6x^2-5)+2(6x^2-5)

2. Facto out the common term 6x^2-5

(6x^2-5)(x^2+2)

Have a nice day :D

ANSWERED AT 28/02/2020 - 04:24 AM

QUESTION POSTED AT 28/02/2020 - 04:24 AM

1 a 2 a 3 d or c because 9times 2 =18 or 6times3=18

ANSWERED AT 28/02/2020 - 04:21 AM

QUESTION POSTED AT 28/02/2020 - 04:21 AM

**Answer:**

See image.

**Step-by-step explanation:**

If there is a whole number multiplied by the x, its a horizontal shrink.

If there is a whole number multiplied by the whole function, its a vertical stretch.

If there is a fraction multiplied by the x, its a horizontal stretch.

If there is a fraction multiplied by the whole function, its a vertical shrink.

ANSWERED AT 28/02/2020 - 04:10 AM

QUESTION POSTED AT 28/02/2020 - 04:10 AM

The Final Result would to your question would be 7x + 2y - 4

i hope this helps you out! :)

i hope this helps you out! :)

ANSWERED AT 28/02/2020 - 04:03 AM

QUESTION POSTED AT 28/02/2020 - 04:03 AM

1-4h^2-12hk-9k^2

-(4h^2+12hk-(1-9k^2))

-(4h^2+12hk-(1^2-(3k)^2))

-(4h^2+12hk-(1+3k)(1-3k))

-4h^2-12hk+(1+3k)(1-3k)

-(4h^2+12hk-(1-9k^2))

-(4h^2+12hk-(1^2-(3k)^2))

-(4h^2+12hk-(1+3k)(1-3k))

-4h^2-12hk+(1+3k)(1-3k)

ANSWERED AT 28/02/2020 - 04:02 AM

QUESTION POSTED AT 28/02/2020 - 04:02 AM

From this we know that x = -8

So all we need to do is plug -8 into the equation everywhere there is an x

So y = -4 * -8 + 3

y = 32 + 3

So y is equal to 35, and since y is the output, the output is 35

So all we need to do is plug -8 into the equation everywhere there is an x

So y = -4 * -8 + 3

y = 32 + 3

So y is equal to 35, and since y is the output, the output is 35

ANSWERED AT 28/02/2020 - 03:38 AM

QUESTION POSTED AT 28/02/2020 - 03:38 AM

To find the slope between 2 points we will use the slop equation

(Y - y)/(X - x)

What this means is that the y part of the first point minus the y part of the second point all divided by the x part of the first point minus the x part of the second point is the slope

So (-4 - -9)/(5 - 8) is the slope

To simplify

-4 minus -9 is 5

And 5 minus 8 is -3

So the slope is 5/-3

Which is -5/3 (negative five thirds)

Feel free to ask questions if you are still confused.

(Y - y)/(X - x)

What this means is that the y part of the first point minus the y part of the second point all divided by the x part of the first point minus the x part of the second point is the slope

So (-4 - -9)/(5 - 8) is the slope

To simplify

-4 minus -9 is 5

And 5 minus 8 is -3

So the slope is 5/-3

Which is -5/3 (negative five thirds)

Feel free to ask questions if you are still confused.

ANSWERED AT 28/02/2020 - 03:38 AM

QUESTION POSTED AT 28/02/2020 - 03:38 AM

The answer to my question is (x)+(y)+4

ANSWERED AT 27/02/2020 - 05:29 PM

QUESTION POSTED AT 27/02/2020 - 05:29 PM